2022
DOI: 10.1007/s00167-021-06857-5
|View full text |Cite
|
Sign up to set email alerts
|

Thromboprophylaxis after knee arthroscopy does not decrease the risk of deep vein thrombosis: a network meta-analysis

Abstract: PurposeThe primary aim of this network meta‐analysis (NMA) is to compare the incidence of venous thromboembolisms (VTE) and bleeding risk following the use of pharmacological and non‐pharmacological thromboprophylaxis for arthroscopic knee surgery (AKS). This study assumed the null hypothesis which was that there will be no difference in the incidence of VTE and bleeding risk when comparing no treatment, pharmacological treatment, and non‐pharmacological treatment for preventing VTE events following AKS. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…It has obvious effects on improving joint wear and meniscus damage, removing abnormal knee joint debris and proliferative tissue, and improving joint mobility. After knee arthroscopy, most patients can effectively control the development of the disease and avoid the need for knee replacement [ 13 , 14 ]. In this study, the WOMAC scores of 41 control patients were significantly reduced after arthroscopic surgery, and the bone metabolism indexes and oxidative stress indexes were well improved, indicating that arthroscopic surgery does have a certain therapeutic effect on KOA patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has obvious effects on improving joint wear and meniscus damage, removing abnormal knee joint debris and proliferative tissue, and improving joint mobility. After knee arthroscopy, most patients can effectively control the development of the disease and avoid the need for knee replacement [ 13 , 14 ]. In this study, the WOMAC scores of 41 control patients were significantly reduced after arthroscopic surgery, and the bone metabolism indexes and oxidative stress indexes were well improved, indicating that arthroscopic surgery does have a certain therapeutic effect on KOA patients.…”
Section: Discussionmentioning
confidence: 99%
“…As DVT protection, IPC was reported as inferior to or equal with placebo treatment after arthroscopic knee surgery. 12,13 Also, IPCþLMWH, compared with LMWH, did not reduce symptomatic DVT after prostatectomy. 14 Further, a small RCT among patients undergoing oesophagectomy found significant lower rates of VTE with LMWH compared with IPC (0 versus 22.6%, P ¼ 0.002) as the primary endpoint.…”
Section: Thromboprophylaxis With Graduated Compression Stockingsmentioning
confidence: 96%
“…The authors reported that at the timepoint of 6 months post‐treatment, platelet‐rich plasma conferred the highest probability of pain reduction followed by plasma rich in growth factors, hyaluronic acid, corticosteroids, and placebo. Lameire et al[6] examined nine randomized controlled trials including 4526 patients to compare the efficacy of various methods in preventing deep vein thrombosis prophylaxis after knee arthroscopy. The authors compared placebo, graduated compression stockings, extended duration (> 10 days) low molecular weight heparin, short duration (< 10 days) low molecular weight heparin, and rivaroxaban.…”
Section: Current Applications Of Network Meta‐analyses In the Orthopa...mentioning
confidence: 99%